Impact and challenges in psychology management of burn injury for adults and children at emergency department - Mohamad, Nasir; Azman, Atikah; Rosly, Haziqah; Krishnasamy, Lingeshree; Abu Bakar, Norsuhaily; Ashaari, Asmidawati (Res Militaris, 2022)
Burns are devastating and debilitating injuries leading to high morbidity and mortality, psychology and emotional stress and add to the financial burden. Severely burned patients should preferably be managed in a burn center with a dedicated intensive care unit (ICU). Severity of burns are classified according to the degree of burns and total body surface area (TBSA) with burns. Rule of nine is used for calculation of TBSA with burn. However, management of burn in adults and children at the emergency department are different. The management of paediatric burns can be a major challenge for the treating unit. One has to keep in mind that "children are not merely small adults"; there are certain features in this age group that warrant special attention. The peculiarities in the physiology of fluid and electrolyte handling, the uniqueness of the energy requirement and the differences in the various body proportions in children dictate that the paediatric burn management should be taken with a different perspective than for adults. This paper will present 5 case series about patient burn in adult and children and will review how challenging hospitals manage these patients.